Magmatic Processes at Snæfell Volcano, Iceland, Constrained by Zircon Ages, Isotopes, and Trace Elements. (9th March 2021) - Banik, Tenley J.; Carley, Tamara L.; Coble, Matthew A.; Hanchar, John M.; Dodd, Justin P.; Casale, Gabriele M.; McGuire, Sean P.
Abstract: We present the first zircon‐based U‐Pb geochronology, trace element concentrations, and O and Hf isotope compositions for Snæfell, an off‐rift volcano in eastern Iceland. These data provide constraints on the longevity and petrogenetic conditions of the Snæfell magmatic system. U‐Pb zircon ages range from 545 ± 59 to 266 ± 16 ka (2SE), but differences between grain core and mantle ages within each sample reveal zircon residence times of 100–200 kyr—far longer than observed at other Neovolcanic systems in Iceland. Zircon δ 18 O is restricted to ∼3.5–4‰, and zircon εHf ranges ∼+13 to ∼+17, which is substantially more radiogenic than Snæfell basalts. This combined O and Hf isotopic perspective suggests rhyolite petrogenesis at Snæfell can be attributed to fractional crystallization of mantle‐derived basaltic magmas with limited influence of pre‐existing crustal material. Trace element evidence further characterizes the magmatic source material: Sc/Yb <∼0.01 suggests an amphibole‐free petrogenetic environment, and Ti concentrations in zircon <5 ppm suggest a cool, near‐solidus, crystallization environment for the majority of the zircon's pre‐eruptive history, with elevated Ti in zircon surfaces suggesting a late thermal perturbation, perhaps a mafic input that remobilized (to the point of eruption triggering) near‐solidus magmas. These zircon‐based conclusions are broadly consistent with previous interpretations of rhyolite petrogenesis conditions at Snæfell but provide a multi‐faceted perspective with more detailed resolution of source materials, magma generating processes, system longevity, and pre‐eruptive conditions. Key Points: First zircon‐based constraints on longevity and petrogenetic processes associated with production of rhyolites at Snæfell volcano, Iceland Zircon crystallization and residence occurs on timescales up to ∼200 kyr at Snæfell—much longer than at other studied Neovolcanic centers Hf and O isotopes in zircon reveal petrogenesis dominated by fractional crystallization of mantle melts with minor crustal assimilation